2018
DOI: 10.3390/su10072181
|View full text |Cite
|
Sign up to set email alerts
|

Study on Air Pollution and Control Investment from the Perspective of the Environmental Theory Model: A Case Study in China, 2005–2014

Abstract: China has been suffering from serious air pollution for years due to rapid industrialization. However, the relationship between China's air pollution and pollution control schemes remains understudied in the Chinese air pollution literature. Using the Environmental Theory Model, this paper studies the relationship between air pollution and control investment in China for the period 2005-2014 and applies the inverse distance weighted interpolation (IDW) and Pearson correlation methods. As a result, this paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Previous researcher (Tung, 1983) noted that a p -value of 2 is the most suitable in the IDW interpolation. The IDW method is used for spatial interpolation in the environmental research of soil properties, terrain mapping, and air pollution (Salekin et al, 2018; Srivastava et al, 2019; Su et al, 2018). In this research, the IDW method has been implemented by ArcGIS with the value of p being 2, and n being 47.…”
Section: Methodsmentioning
confidence: 99%
“…Previous researcher (Tung, 1983) noted that a p -value of 2 is the most suitable in the IDW interpolation. The IDW method is used for spatial interpolation in the environmental research of soil properties, terrain mapping, and air pollution (Salekin et al, 2018; Srivastava et al, 2019; Su et al, 2018). In this research, the IDW method has been implemented by ArcGIS with the value of p being 2, and n being 47.…”
Section: Methodsmentioning
confidence: 99%
“…In these regions, the whole society electricity consumption and vehicle ownership also play a positive role in air pollution [46]. The region used to have the most severe air pollution in China, and even the world [47][48][49]. The residents in investigation regions have a deeper and clearer understanding of air pollution [50].…”
Section: Region Descriptionmentioning
confidence: 99%
“…This nding demonstrated that the industrial pollution management investment and production structure is irrational and ine cient. Su et al (2018) investigated the relationship between air pollution and air pollution control investment in China from 2005 to 2014 using inverse distance weighted interpolation (IDW) and Pearson correlation approaches. The research found a relationship between China's air pollution index (API) and pollution mitigation investment.…”
Section: Introductionmentioning
confidence: 99%